Perceptions of Pre-Service English Teachers on Using ChatGPT for Lesson Planning - Sukmadana, Salsa Rahmatullah; Halim, Abdul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines Indonesian pre-service English teachers’ perceptions of using ChatGPT as a support tool for lesson planning. While generative artificial intelligence has gained increasing attention in education, empirical evidence from EFL teacher education contexts in Indonesia remains limited. Employing an explanatory sequential mixed-methods design, this study collected quantitative data through a structured questionnaire administered to 30 pre-service English teachers enrolled in an English Education program at a private university in Indonesia. Descriptive statistics were used to identify general perception patterns. To further explain the survey results, qualitative data were obtained through semi-structured interviews with three selected participants and analyzed using thematic analysis. The findings indicate that most participants perceive ChatGPT as beneficial for generating lesson ideas, structuring lesson components, and saving preparation time. ChatGPT was also reported to support confidence and professional learning, particularly for pre-service teachers with limited teaching experience. However, the results simultaneously reveal critical concerns, including repetitive outputs, limited contextual suitability, potential inaccuracies, and the need for substantial revision of AI-generated lesson plans. Importantly, participants consistently emphasized that ChatGPT should function as a supportive assistant rather than a replacement for teachers’ professional judgment. This study contributes to the growing body of research on generative AI in teacher education by providing context-specific insights from the Indonesian EFL setting. The findings highlight the importance of integrating AI literacy into pre-service teacher education to promote critical, ethical, and pedagogically sound use of generative AI tools.